Correlational and Comparative Designs as Quantitative Research Approaches - Ahmad Rifa’i; Luqman Hakim Wahyudi; Nabila Aulia Rahmah; Syarla Nur Fitra Aura; Bayu Bambang Nur Fauzi (Penerbit Hellow Pustaka, 2026)
This study aims to examine two widely used approaches in quantitative research, namely Correlational Design and Comparative Design. The discussion focuses on understanding the concepts, characteristics, operational procedures, and practical applications of both research Designs in educational and social science studies. The research employed a library research method with a descriptive qualitative approach by reviewing relevant books, scientific journals, and methodological references. The findings indicate that Correlational Design is used to identify and analyze relationships among variables without any researcher intervention, enabling the exploration of association patterns and the prediction of certain phenomena. Meanwhile, Comparative Design is intended to compare two or more naturally existing groups in order to identify similarities and differences in specific variables. Although both approaches do not involve experimental manipulation, they differ in their primary focus. Correlational Design emphasizes the strength and direction of relationships among variables, whereas Comparative Design concentrates on differences between groups. Therefore, a comprehensive understanding of these two research Designs is essential for researchers in selecting the most appropriate method according to their research objectives and in producing valid, reliable, and scientifically accountable findings.